2006
DOI: 10.1080/00365510600873894
|View full text |Cite
|
Sign up to set email alerts
|

Achlorhydria is associated with gastric microbial overgrowth and development of cancer: Lessons learned from the gastrin knockout mouse

Abstract: Gastrin and gastrin receptor-deficient mice have been used for genetic dissection of the role of gastrins in maintaining gastric homeostasis and control of acid secretion. The gastrin knockout mice are achlorhydric due to inactivation of the ECL and parietal cells. Moreover, this achlorhydria is associated with intestinal metaplasia and bacterial overgrowth, which ultimately leads to the development of gastric tumours. The association between progastrin, progastrin-derived processing intermediates and colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 118 publications
0
24
0
3
Order By: Relevance
“…miR-24 is likely to predominantly operate by inhibiting translation. In addition, alkalization of the environment around the gastric epithelium may also take part in the induction of AE1 expression (Friis-Hansen, 2006). These data provide new insights into the molecular mechanisms of human erythropoiesis and gastric tumorigenesis.…”
Section: Discussionmentioning
confidence: 86%
“…miR-24 is likely to predominantly operate by inhibiting translation. In addition, alkalization of the environment around the gastric epithelium may also take part in the induction of AE1 expression (Friis-Hansen, 2006). These data provide new insights into the molecular mechanisms of human erythropoiesis and gastric tumorigenesis.…”
Section: Discussionmentioning
confidence: 86%
“…41 Analogous to the studies in mice, hypochlorhydria in human patients with atrophic gastritis or following an antrectomy has also been reported result in an increased risk for developing gastric cancer, with most of the risk attributed to bacterial overgrowth as well as generation of carcinogenic substances such as N-nitrosamines, which can be found in increased amounts in hypochlorhydric patients. 42,43 We also recently reported that antibiotics treatment of H. pylori infected INS-GAS mice on an FVB/N background had an effect on arresting progression of gastric lesions. 18 Overall, the data taken together are consistent with a model in which gastrin serves as a rheostat for the stomach.…”
Section: Discussionmentioning
confidence: 89%
“…Gastrin-deficient mice develop antral adenocarcinomas [46] through a mechanism that must be different from carcinogenesis in the oxyntic mucosa in hypoacidic and hypergastrinemic mice. The development of carcinomas in the absence of gastrin is attributed to bacterial overgrowth and subsequent formation of carcinogenic substances [47,48] . However, gastric hypoacidity is also found in H + K + ATPase-deficient mice which do not develop antral carcinomas (Fossmark R et al unpublished observations) and it is possible the lack of gastrin itself induces the carcinomas.…”
Section: Neoplasiamentioning
confidence: 99%